Disparities in Care for Publicly Insured Women With Pregestational Diabetes. Issue 5 (November 2017) - Easter, Sarah Rae; Rosenthal, Emily W.; Morton-Eggleston, Emma; Nour, Nawal; Tuomala, Ruth; Zera, Chloe A.
Abstract : OBJECTIVE: To investigate the association among public health insurance, preconception care, and pregnancy outcomes in pregnant women with pregestational diabetes. METHODS: This is a retrospective cohort of pregnant women with pregestational type 1 or type 2 diabetes from 2006 to 2011 in Massachusetts—a state with universal insurance coverage since 2006. Women delivering after 24 weeks of gestation and receiving endocrinology and obstetric care in a multidisciplinary clinic were included. Rates of preconception consultation, our primary outcome of interest, were then compared between publicly and privately insured women. We used univariate analysis followed by logistic regression to compare receipt of preconception consultation and other secondary diabetes care measures and pregnancy outcomes according to insurance status. RESULTS: Fifty-four percent (n=106) of 197 women had public insurance. Publicly insured women were younger (median age 30.4 compared with 35.3 years, P <.01) with lower rates of college education (12.3% compared with 45.1%, P <.01). Women with public insurance were less likely to receive a preconception consult (5.7% compared with 31.9%, P <.01), had lower rates of hemoglobin A1C less than 6% at the onset of pregnancy (37.2% compared with 58.4%, P =.01), and experienced higher rates of pregnancies affected by congenital anomalies (10.4% compared with 2.2%, P =.02) compared with those with private insurance. In adjusted analyses controlling for educational attainment, maternal age, and body mass index, women with public insurance were less likely to receive a preconception consult (adjusted odds ratio [OR] 0.21, 95% CI 0.08–0.58), although the odds of achieving the target hemoglobin A1C (adjusted OR 0.45, 95% CI 0.20–1.02) and congenital anomaly (adjusted OR 2.23, 95% CI 0.37–13.41) were similar after adjustment. CONCLUSION: Despite continuous access to health insurance, publicly insured women were less likely than privately insured women to receive a preconception consult—an evidence-based intervention known to improve pregnancy outcomes. Improving use of preconception care among publicly insured women with diabetes is critical to reducing disparities in outcomes. Abstract : With universal access to health care, publicly insured pregnant women with pregestational diabetes have lower rates of preconception care than privately insured pregnant women.